THE EFFECT OF 6-WEEKS WHOLE BODY VIBRATION ON MUSCULAR PERFORMANCE ON YOUNG NON-COMPETITIVE FEMALE ARTISTIC GYMNASTS - George Dallas; Alkmini Savvathi; Konstantinos Dallas; Maria Maridaki (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
The purpose of this study was to investigate the effects of a 6-week whole body vibration-intervention on muscle performance and flexibility on gymnasts. Twenty-two young non-competitive-moderate trained gymnasts that volunteered to participate in the study separated into either the vibration group or the no vibration group according to their training regime. The vibration intervention consisted of a 6-week whole-body vibration, 3 times per week and involved eccentric and concentric squatting movements on a vibration platform with the participants performing three exercises on the vibration device whereas for the no vibration group vibration platform was turned off. Five performance tests (20m running speed, sit & reach test, squat jump, counter movement jump and single leg squat (right leg and left leg) were performed at the beginning of the intervention, and after the end of 6-week intervention program. According to the results significant interaction effect between group and time was found for the running speed and Squat Jump test. On the contrary, significant main effect were found were found for time on the running speed, Squat Jump, Counter movement jump and single leg squat. Conclusively, it has been reported that Whole body vibration is an effective method to improve Squat Jump performance in young non-competitive female artistic gymnasts.